Local decision makers' awareness of the social determinants of health in Turkey: a cross-sectional study - Didem Evci (Kiraz); Filiz Ergin; Orhan Okur; Gulnur Saruhan; Erdal Beser (BMC, 2012)
Abstract Background Social determinants have been described as having a greater influence than other determinants of health status. The major social determinants of health and the necessary policy objectives have been defined; it is now necessary to evaluate the effectiveness of these policies. Previous studies have shown that descriptions of the awareness level of citizens and local decision makers, practice-based research and evidence, and intersectoral studies are the best options for investigating the social determinants of health at the community level. The objective of the present study was to define local decision makers' awareness of the social determinants of health in the Aydin province of Turkey. Methods A total of 53 mayors serve the Aydin city center, districts and towns. Aydin city center has 22 neighborhoods and 22 headmen responsible for them. The present study targeted all mayors and headmen in Aydin - a total of 75 possible participants. A questionnaire was used to collect the data. The questionnaire was faxed to the mayors and administered face-to-face with the headmen. Results Headmen identified the three most important determinants of public health as environmental issues, addictions (smoking, alcohol) and malnutrition. According to the mayors, the major determinant of public health is stress, followed by malnutrition, environmental issues, an inactive lifestyle, and the social and economic conditions of the country. Both groups expressed that the Turkish Ministry of Health, municipalities and universities are the institutions responsible for developing health policy. Headmen were found to be unaware and mayors were aware of the social determinants of health as classified by the World Health Organisation. Both groups were classified as unaware with regard to their awareness of the Marmot Review policy objectives. Conclusions Studies such as the present study provide important additional information on the social determinants of health, and help to increase the awareness levels of both local decision-makers and the community. Such studies must be considered a vital first step in future public health research on health determinants and their impact on national and international policies.